Okun's Law and Long Term Co-Integration Analysis for OECD Countries (1987-2012) - Bilal KARGI (International Research Journal of Finance and Economics, 2014)
Even though, there are so many so long discussions on the relation between population increase and economic growth, today, general opinion tends to believe that there is a direct relation between population increase and economic growth. This opinion is supported by some empirical studies. Despite an economical growth caused by directly with population growth, it is known that there is a reverse relation between unemployment and growth known as Okun's Law. This relation, suggesting that every 1 point decrease in unemployment induces a 3 point increase in growth, is tested for many countries. In this study, this hypothesis of Okun is examined and it is found to be true for selected 23 countries, even with the difference in coefficients. At the same time, long term relation between growth and unemployment is tested with the use of time series analysis and long term relation is found for 14 countries. Additionally, tests done for all 34 OECD countries showed that reversed relation between unemployment and growth is valid and they are cointegrated in long run. In this study, countries are categorized according to growth rate as “low”, “normal” and “high” and a consistent unemployment rate for countries with high growth rate could not be seen. In the case of countries with lowest growth rate, generalization that they have quite high unemployment rate can be made.
Keywords: O40; O57; J64; 330; Economic Growth; OECD Countries; Unemployment